Fixed point theorems by ways of ultra-asymptotic centers - Dhompongsa S. (2014)
We use an approach on ultra-asymptotic centers to obtain fixed point theorems for two classes of nonself multivalued mappings. The results extend and improve several known ones. © 2011 S. Dhompongsa and N. Nanan.